2012
DOI: 10.1007/s10551-012-1461-9
|View full text |Cite
|
Sign up to set email alerts
|

Women in the Boardroom: How Do Female Directors of Corporate Boards Perceive Boardroom Dynamics?

Abstract: This study investigated how female directors of corporate boards of directors (BoD) experience boardroom dynamics. The study represents an initial research trend that moves from a unilateral focus on financial outcomes of female representation in BoDs toward stronger attention on the social dynamics in the boardroom. Drawing on social identity theory, the study proposed that female directors often constitute an out-group within the BoD, preventing them from experiencing positive board dynamics. More specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
1
36
1
3
Order By: Relevance
“…The main reason appears to be that a team with higher member homogeneity is more likely to cooperate and less prone to emotional conflicts (Earley and Mosakowski, 2000). Thus, members of a diverse group are more likely to experience a lack of cohesion, communication, and cooperation, which in turn heightens the potential for dissatisfaction and conflict (Shapcott, Carron, Burke, Bradshaw, and Estabrooks, 2006;Mathisen, Ogaard, and Marnburg, 2013). In such situations, the team requires more time and effort to reach a consensus.…”
Section: Negative Relationshipmentioning
confidence: 99%
“…The main reason appears to be that a team with higher member homogeneity is more likely to cooperate and less prone to emotional conflicts (Earley and Mosakowski, 2000). Thus, members of a diverse group are more likely to experience a lack of cohesion, communication, and cooperation, which in turn heightens the potential for dissatisfaction and conflict (Shapcott, Carron, Burke, Bradshaw, and Estabrooks, 2006;Mathisen, Ogaard, and Marnburg, 2013). In such situations, the team requires more time and effort to reach a consensus.…”
Section: Negative Relationshipmentioning
confidence: 99%
“…For instance, evidence from low-and middle-income countries suggests that gender-empowering initiatives such as promoting women in leadership and senior management bolsters revenue, efficiency, and productivity (Edwards 2017). Gender diversity in corporate boards has also proved to have incremental benefits on a broad range of outcomes, including better boardroom dynamics/effectiveness and overall financial performance (Adams and Ferreira 2009, Arena et al 2015, Mathisen et al 2013, Nielsen and Huse 2010. A study of firms with shares listed in Singapore found that greater gender diversity improved firm performance as measured by returns on assets and equity (Dieleman et al 2013).…”
Section: The Strong Economic Case For Leveraging Women's Entrepreneurmentioning
confidence: 99%
“…For instance, evidence from low-and middle-income countries suggests that gender-empowering initiatives such as promoting women in leadership and senior management positions bolstered revenue, efficiency, and productivity (Edwards 2017). Moreover, gender diversity in corporate boards and/or increasing the leadership of women executives prove to have incremental benefits on a broad range of corporate outcomes, including improved boardroom dynamics and effectiveness and overall firm financial performance (Adams and Ferreira 2009;Adusei and Yaa Takyiwah Obeng 2019;Arena et al 2015;Chandani, Mehta, and Chandrasekaran 2014;Mathisen, Ogaard, and Marnburg 2013;Mohan 2014;Nielsen and Huse 2010). Proactive policy support and affirmative measures to mainstream and upscale women's economic participation is vital not only to fully maximize their potential contributions but also to cultivate a vibrant private sector.…”
Section: Supporting the Internationalization Of Msmes And Women-ownedmentioning
confidence: 99%